Quantum Physics and Linguistics 2013
DOI: 10.1093/acprof:oso/9780199646296.003.0007
|View full text |Cite
|
Sign up to set email alerts
|

Scalars, Monads, and Categories

Abstract: The paper describes interrelations between: (1) algebraic structure on sets of scalars, (2) properties of monads associated with such sets of scalars, and (3) structure in categories (esp. Lawvere theories) associated with these monads. These interrelations will be expressed in terms of "triangles of adjunctions", involving for instance various kinds of monoids (non-commutative, commutative, involutive) and semirings as scalars. It will be shown to which kind of monads and categories these algebraic structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 14 publications
0
43
0
Order By: Relevance
“…In [13] it is shown that a monad S is additive iff the coproducts (0, +) of its Kleisli category K (S) are biproducts iff the products (1, ×) of its category EM(S) of Eilenberg-Moore algebras are biproducts.…”
Section: Examplementioning
confidence: 99%
See 1 more Smart Citation
“…In [13] it is shown that a monad S is additive iff the coproducts (0, +) of its Kleisli category K (S) are biproducts iff the products (1, ×) of its category EM(S) of Eilenberg-Moore algebras are biproducts.…”
Section: Examplementioning
confidence: 99%
“…An effectus is a relatively simple category, with finite coproducts and a final object, satisfying some elementary properties: certain squares have to be pullbacks and certain parallel maps have to be jointly monic, see (25) and (13) below. These effectuses have been introduced in [30], and give rise to a rich theory that includes quantum computation, see the overview paper [10].…”
Section: Introductionmentioning
confidence: 99%
“…Given a simple Segala system c : X → P(A × DX), its EM-extension F EM (c) from Lemma 3, obtained via the EM-law ρ from (8), is the same as the coalgebra c # : DX → P(A × DX) described in Equation (7).…”
Section: Simple Segala Systems In Em-stylementioning
confidence: 99%
“…The extension natural tranformation follows from additivity of the multiset monad M C (like in (2), see [8]), in:…”
Section: Weighted Automatamentioning
confidence: 99%
“…-Fundamental to our approach is a (partial) semiring structure on the set T1, studied in [8,3,2]. On the one hand, its (partial) addition operation induces an order on T1 which is used to generalise the notion of predicate typically employed in the semantics of modal logics, by considering predicates valued in T1.…”
Section: Introductionmentioning
confidence: 99%